Kebijakan Penerapan Hukuman Mati Terhadap Pelaku Korupsi Perspektif Hak Asasi Manusia (HAM) di Indonesia - Fanisya Nurmadina (Universitas Kuningan, 2025)
The purpose of this article is to explore the conflict between basic human rights principles and the death penalty policy applied to corruption perpetrators in Indonesia. One of the human rights principles is the right to life, which is guaranteed by various international conventions. Therefore, this paper can focus on whether the death penalty is properly implemented and whether the sanctions imposed provide a deterrent effect or actually create injustice. The method used in this paper uses a normative juridical study that focuses on applicable legal norms, both written and unwritten, in an effort to understand and analyze legal issues. The results of the discussion are that the death penalty for corruption perpetrators in Indonesia is regulated by Law No. 20 of 2001 concerning Amendments to Law No. 31 of 1999 concerning the Eradication of Corruption. Although the death penalty can be imposed under certain conditions, its application faces controversy related to human rights violations, particularly the right to life. In addition, the imbalance between state losses and sanctions imposed, as well as international pressure from the UN to abolish the death penalty, pose challenges in implementing this policy. The conclusion shows that the death penalty is difficult to determine because Article 2 paragraph (2) of the Corruption Law states that the death penalty can be imposed if the crime of corruption is committed under certain circumstances, which refers to situations that make the crime of corruption more serious, such as corruption committed in emergency situations or natural disasters.